Magnetic structure analysis of the L21-type austenite in Ni–Mn–In alloys - Lopez García, J.; Khanna, D. L. R.; Sanchez Llamazares, J. L.; Álvarez Alonso, P.; la Roca, Paulo Matías; Recarte, V.; Sánchez Alarcos, V.; Pérez Landazábal, J. I.; Rodríguez Velamazán, J. A. (Elsevier, 2024)
Fil: Lopez García, J.. Universidad Pública de Navarra; España